STRATEGI KEPALA MADRASAH DALAM MELAKSANAKAN SISTEM PENJAMINAN MUTU INTERNAL DI MADRASAH IBTIDAIYAH NEGERI 1 BATANG HARI - Amrizal; Sukatin; Afiyah, Zahratul; Hikmah, Sadratul; Fitri, Julia (Department of Islamic Education Management, 2024)
This article was written to find out the strategy of madrasah heads in implementing an internal quality assurance system. The research method used is qualitative research with data collection techniques through observation and interviews. The subjects of this research were madrasa principals, deputy principals and teaching staff. The strategy used by the madrasa head in quality mapping is to create a school self-evaluation document through planning for quality fulfillment, including building a vision, mission, madrasa work plan, socializing it to stakeholders, forming a quality assurance team. The strategy carried out by the Head of the Madrasah in implementing the quality fulfillment plan is by implementing the madrasah work plan and carrying out evaluations by monitoring and evaluating periodically, such as every third month, semester and yearly and on an ongoing basis. The strategy for establishing new quality standards at Madrasah Ibtidaiyah Negeri 1 Batang Hari is to improve the quality of human resources, the quality of graduates, and the quality of facilities and infrastructure. With the existence of an internal quality assurance system at Madrasah Ibtidaiyah Negeri 1, it is hoped that the goals of the national education system can be achieved.